Effect of gamal leaves (Gliricidia sepium ) extract against termite (Coptotermes curvignathus) - Pratiwi, Baiq Yulia Hasni; Muhsin, Lalu Busyairi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The World Health Organization (WHO) estimates around 3 million people working in the agricultural sector experience insecticide poisoning, and 18 thousand of them die every year. The massive use of synthetic insecticides can harm non-targeted organisms such as plants and livestock. Moreover, this may lead to ecological imbalance and increase pollution. Thus, there is a need for innovation in making natural insecticides. Indonesia is home to abundant plant diversity; one of those is the Gamal plant (Gliricidia sepium). Previous studies found that Gamal leaves contain secondary metabolites such as flavonoids, alkaloids, tannins, saponins, and steroids. Flavonoids are known to have a toxic effect on mealybugs in the papaya plant, and tannins are antimicrobial and often used as pest control. Based on this, the Gamal plant has potential as a natural insecticide. One of the most critical pests in agriculture and households is termites (Coptotermes curvignathus), which often cause losses by damaging plants and household furniture. Also, there is no research yet on Gamal leaves against termites. Therefore, research is necessary to test the effectiveness of Gamal leaf extract against termites. In this study, experimental research was used with a quantitative approach. The Gamal leaf extract was obtained using ethanol and methanol solvents through a maceration technique. Several termites were acclimatized, and 120 were taken randomly for toxicity testing. Four concentrations (10%, 25%, 50%, and 75%) were applied to each group of ten termites. This treatment was repeated three times, and the termite mortality time was measured. Afterwards, the value of LC50 was determined using a regression line between log concentration and probit mortality. The result shows that the higher the concentration, the shorter the termite death time. The mortality rate reaches 100% within 1 to 2 minutes after treatment. The LC50 value of Gamal leaves extract against termites obtained is 5,1%. This indicates that Gamal leaves are very effective in killing termites, even in the lowest concentration. It is likely caused by secondary metabolites, especially flavonoids, that have insecticidal effects. In brief, the ethanolic and methanolic extract of Gamal leaves has the potential to be a natural insecticide to substitute synthetic insecticide, which is safer, economical, and environmentally friendly.